Examining the Concept of Healthcare Trajectories in Older Adults With Major Neurocognitive Disorder Using the ‘6W’ Multidimensional Model of Care Trajectories: A Mixed Methods Systematic Review Protocol - Dufour, Isabelle; Bolster-Foucault, Clara; Vedel, Isabelle; Quesnel-Vallée, Amélie (Science of Nursing and Health Practices / Science infirmière et pratiques en santé)

(untitled) (Réseau de recherche en interventions en sciences infirmières du Québec (RRISIQ), 2021)
Introduction: The use of healthcare services by older adults with major neurocognitive disorder (MNCD) varies significantly throughout the disease process. The evaluation of healthcare trajectories, defined as the pattern of care use over time, allows for a better understanding of how people move through the healthcare system and facilitates the identification of potentially modifiable risk factors for suboptimal care trajectories. Objectives: The objectives of the review are to: 1) critically appraise and synthesize evidence on how healthcare trajectories of older adults with MNCD are measured and defined, using the ‘6W’ multidimensional model of care trajectories, and 2) examine how socioeconomic factors are considered in studies reporting on healthcare trajectories. Inclusion criteria: This review will consider community-dwelling older adults diagnosed with MNCD. The quantitative component will include studies reporting on healthcare trajectories, including at least 2 different care services and at least 3 time-points. The qualitative component will include studies reporting on healthcare trajectories from the perspective of patients or their informal caregivers. Methods: This review will follow the Joanna Briggs Institute mixed methods review approach. We will search EMBASE, MEDLINE, CINAHL, PsycINFO, and the Web of Science Core Collection for English or French articles. Independent reviewers will identify articles for inclusion, extract data, and assess quality. A convergent integrated approach to synthesis and integration will be used. Discussion and conclusion: The results will help anticipate patients’ needs, improve patient care, service planning and coordination, and understand inequities in MNCD care.